Comparison of organ-specific-radiation dose levels between 70 kVp perfusion CT and standard tri-phasic liver CT in patients with hepatocellular carcinoma using a Monte-Carlo-Simulation-based analysis platform. (2016) - Gawlitza, J.; Haubenreisser, H.; Meyer, M.; Hagelstein, C.; Sudarski, S.; Schoenberg, S.O.; Henzler, T.
Abstract: Purpose: The aim of this study was to systematically compare organ-specific-radiation dose levels between a radiation dose optimized perfusion CT (dVPCT) protocol of the liver and a tri-phasic standard CT protocol of the liver using a Monte-Carlo-Simulation-based analysis platform. Methods and materials: The complete CT data of 52 patients (41 males; mean age 65 ± 12) with suspected HCC that underwent dVPCT examinations on a 3rd generation dual-source CT (Somatom Force, Siemens) with a dose optimized tube voltage of 70 kVp or 80 kVp were exported to an analysis platform (Radimetrics, Bayer). The dVPCT studies were matched with a reference group of 50 patients (35 males; mean age 65 ± 14) that underwent standard tri-phasic CT (sCT) examinations of the liver with 130 kVp using the calculated water-equivalent-diameter of the patients. The analysis platform was used for the calculation of the organ-specific effective dose (ED) as well as global radiation-dose parameters (ICRP103). Results: The organ-specific ED of the dVPCT protocol was statistically significantly lower when compared to the sCT in 14 of 21, and noninferior in a total of 18 of 21 examined items (all p < 0.05). The EDs of the dVPCT examinations were especially in the dose sensitive organs such as the red marrow (17.3 mSv vs 24.6 mSv, p = < 0.0001) and the liver (33.3 mSv vs 46.9 mSv, p = 0.0003) lower when compared to the sCT. Conclusion: Our results suggest that dVPCT performed at 70 or 80 kVp compares favorably to sCT performed with 130 kVp with regard to effective organ dose levels, especially in dose sensitive organs, while providing additional functional information which is of paramount importance in patients undergoing novel targeted therapies.